2022
DOI: 10.1038/s41598-022-09981-5
|View full text |Cite
|
Sign up to set email alerts
|

NT3 treatment alters spinal cord injury-induced changes in the gray matter volume of rhesus monkey cortex

Abstract: Spinal cord injury (SCI) may cause structural alterations in brain due to pathophysiological processes, but the effects of SCI treatment on brain have rarely been reported. Here, voxel-based morphometry is employed to investigate the effects of SCI and neurotrophin-3 (NT3) coupled chitosan-induced regeneration on brain and spinal cord structures in rhesus monkeys. Possible association between brain and spinal cord structural alterations is explored. The pain sensitivity and stepping ability of animals are coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 75 publications
(105 reference statements)
0
4
0
Order By: Relevance
“…A previous research has shown that SCI can induce changes in the central gray caudal to injury that reduces the inhibitory of the gamma‐aminobutyric acid (GABA) receptor and removes a brake on neural activity, allowing a state of over‐excitation 18 . The caudate nucleus is a key hub of striatum, which affects movement by thalamic cortical projection 8,19 . It plays an important role in the maintenance of trunk and limb posture, as well as the accuracy and speed of directional movement 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous research has shown that SCI can induce changes in the central gray caudal to injury that reduces the inhibitory of the gamma‐aminobutyric acid (GABA) receptor and removes a brake on neural activity, allowing a state of over‐excitation 18 . The caudate nucleus is a key hub of striatum, which affects movement by thalamic cortical projection 8,19 . It plays an important role in the maintenance of trunk and limb posture, as well as the accuracy and speed of directional movement 19 .…”
Section: Discussionmentioning
confidence: 99%
“…18 The caudate nucleus is a key hub of striatum, which affects movement by thalamic cortical projection. 8,19 It plays an important role in the maintenance of trunk and limb posture, as well as the accuracy and speed of directional movement. 19 The thalamus is an important relay station which receives sensory and motor information, then processes the signals and transmits it to the cerebral cortex.…”
Section: Alteration Of Sensory Motor Related Brain Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the mouse, cellular delivery of NT3 promotes corticospinal axonal growth and partial functional recovery after spinal cord injury [ 55 ]. Indeed, NT3 can be used to enable chronic-SCI repair and MR-DTI-based mapping of lesion areas [ 56 ]. Relative to the role of NT4 in the spinal cord, previous studies showed that, in synergy with BDNF, it could play a crucial role during axon regeneration and motor neuron plasticity [ 57 , 58 , 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Freund et al [101] also confirmed the presence of structural atrophy of the sensory and motor cortex in patients with chronic cervical SCI, and this condition is closely related to the degree of dysfunction and recovery. The deterioration of cortical structural integrity reduces the processing speed and functional integration of the brain, leading to the deterioration of walking function and neuropathic pain after SCI [6,102].…”
Section: Effect Of Rehabilitation Training On the Structural Remodeli...mentioning
confidence: 99%